Chemical composition and antioxidant properties of some industrial tree bark extracts - Hamad, Ahmed M. A.; Ates, Saim; Olgun, Çağrı; Gür, Mahmut (BioResources, 2019)
Wood bark is a residue of forestry production that is used as a fuel source. The chemical composition of tree bark is similar to that of the harvested wood, and it contains a variety of useful compounds. To determine the chemical composition and antioxidant activities of different barks, fir (Abies nordmanniana), beech (Fagus orientalis), pine (Pinus sylvestris), poplar (Populus alba), and oak (Quercus robur) barks were selected because they are used for industrial purposes in Turkey. The dried bark powders were extracted using a 65:35 methanol-water mixture (v/v) to determine the total phenolic content, the flavonoid content, and the antioxidant properties (2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), metal chelating, and H2O2 scavenging). The flavonoid components were analyzed by high performance liquid chromatography (HPLC) and extracted by hexane to analyze the volatile components by gas chromatography-mass spectrometry (GC-MS). The poplar bark extracts had the highest total phenolic content, highest total flavonoid content, and highest antioxidant content. The poplar bark extracts were rich in myricetin (87.761 mg/L), which is a flavonoid with rich antioxidant properties. The presence of valuable extracts suggests that barks may have uses as valuable raw materials for chemical applications such as cosmetics, perfumes, and food preservatives.
Keywords: 15. Life on land